2000
DOI: 10.1021/ja994282i
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Base Lesions Are Generated by Hydroxyl Radical within Isolated DNA in Aerated Aqueous Solution

Abstract: The hydroxyl radical-mediated formation of two tandem base lesions within DNA including N-(2deoxy-β-D-erythro-pentofuranosyl)formylamine-8-oxo-7,8-dihydro-2′-deoxyguanosine (dβF-8-oxodGuo) and 8-oxodGuo-dβF is reported in this study. A specific enzymatic processing was developed to quantitatively release the tandem lesions as dinucleoside monophosphates from DNA. Then, the resulting hydrolyzed DNA samples were analyzed using liquid chromatography coupled to electrospray ionization tandem mass spectrometry. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 31 publications
3
71
0
2
Order By: Relevance
“…In addition, clustered lesions consisting of L and Tg on opposite strands were studied in order to compare to the tandem lesions. The same local sequences were incorporated into 16-nucleotide long duplexes (12)(13)(14)(15)(16)(17)(18)(19) in order to probe the effects of the lesions on thermal stability.…”
Section: Oligonucleotide Substrate Design and Synthesismentioning
confidence: 99%
“…In addition, clustered lesions consisting of L and Tg on opposite strands were studied in order to compare to the tandem lesions. The same local sequences were incorporated into 16-nucleotide long duplexes (12)(13)(14)(15)(16)(17)(18)(19) in order to probe the effects of the lesions on thermal stability.…”
Section: Oligonucleotide Substrate Design and Synthesismentioning
confidence: 99%
“…Recent works have demonstrated that in dinucleoside monophosphates (11,12) and in oligonucleotides (11,13) peroxyl radicals of pyrimidine bases could efficiently react with a vicinal DNA base. Indeed, it has been recently reported that in DNA addition of pyrimidine peroxyl radicals onto the C8 of a purine base is capable of producing 8-oxodGuo involved in tandem lesions neighboring a formylamine (dF) residue (14,15). Quantitatively, formation of 8-oxodGuo/dF tandem lesions accounts for ∼10% of the generated 8-oxodGuo.…”
mentioning
confidence: 99%
“…The ligation mechanism involves three steps: (a) activation of the enzyme by adenylation (30), (b) formation of the intermediate by transfer of the AMP residue from the enzyme to the 5′-phosphate of the nicked DNA (30), and (c) sealing of the DNA by a transesterification reaction (28,31). The existence of clustered DNA damage (32)(33)(34)(35) and the insertion of dOGMP during replication suggests the possibility that an oxidized lesion could appear near a nick site. Furthermore, the DNA repair enzyme MutY excises adenine opposite guanine or 8-oxoG during BER (11,36,37), and complete repair requires the further action of a polymerase for insertion of dCTP opposite OG, followed by ligation (38).…”
mentioning
confidence: 99%